Hermeneutics, Revelation, and the Critique of Religious Authority: Understanding Shabestari’s Intellectual Reform Project - Fakhri Afif (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This study aims to examine Mohammad Mojtahed Shabestari’s intellectual reform in post-revolutionary Iran by investigating how the qerā’at-e rasmī (official reading) becomes plausible and how it can be theologically dismantled. Using a qualitative conceptual-textual analysis of Shabestari’s major works, supported by selected secondary literature, the article reconstructs his shift from a dictation model of waḥy to revelation as dialogical prophetic experience (blick) and the Qur’an as the Prophet’s historically mediated reading of the world. It then explicates a dual-layer hermeneutics (prophetic and communal) and argues that hermeneutics functions as a foundational epistemic framework for tafsīr, fiqh, and kalām. The findings indicate that Shabestari’s project delegitimizes interpretive monopoly, enables contextual ijtihād, and supports interpretive pluralism and political minimalism centered on freedom of faith. A procedural reading of qiṣāṣ illustrates how the model can yield restorative, dignity-oriented normative outputs. The novelty lies in integrating Shabestari’s revelation theory and authority critique into a single hermeneutical canvas with demonstrable ethical, legal, and political consequences.